Arthralgia adverse events due to immune-checkpoint inhibitors for lung cancer patients: a systematic review and meta-analysis - Zou, Defang; Wang, Xiaoping; Sun, Yamin; Wang, Xi; Lu, Chang; Wang, Aiyun; Wang, Xia; Yang, Yan (Frontiers in Oncology, 2023)
Background Immune agents targeting Programmed cell death-1 (PD-1) are a new type of cancer treatment drugs. By inhibiting the interaction between PD-1 and PD-L1, the ability of the immune system to attack tumor cells is enhanced. These immune preparations have shown significant efficacy in the treatment of various malignant tumors. However, like other drugs, immune preparations targeting PD-1 may also cause side effects, including arthralgia. Therefore, we conduct a meta-analysis to assess whether immune-checkpoint inhibitors targeting programmed cell death-1 in lung cancer patients will lead to arthralgia adverse events. Methods We conducted a comprehensive search across multiple databases, including PubMed, Medline (Ovid), Web of Science, Cochrane, Embase, Scopus, CKNI, Wang fang, VIP database, Sino Med, and Clinical Trails, to identify relevant studies. The search encompassed articles published up until June 20th, 2023. The primary outcome is adverse events about arthralgia and secondary outcomes are any other related with arthralgia. Data extraction was carried out by two independent individuals, and the Cochrane Risk of Bias tool version 2.0 was employed to assess the included studies. The systematic review and meta-analysis were conducted using RevMan 5.3 software. Results 12 studies are included in the meta-analysis. All included studies were determined to have a low risk of random sequence generation bias. The meta-analysis result showed that arthralgia RR = 1.11, 95% CI [0.88, 1.40], I2 = 56%, back pain RR = 1.86, 95% CI [1.07, 3.26], I2 = 84%, myalgia RR = 0.49, 95% CI [0.27, 0.88], I2 = 86% and muscular pain RR = 1.97, 95% CI [1.40, 2.77], I2 = 23%. Conclusion The use of targeted inhibitors may lead to an increased incidence of back pain, while potentially reducing the occurrence of myalgia. On the other hand, immune-checkpoint inhibitors targeting programmed cell death-1 in lung cancer patients may not cause arthralgia and muscular pain.